Changes in cardiac arrest patients' temperature management after the publication of 2015 AHA guidelines for resuscitation in China. Issue 1 (December 2017) - Du, Lanfang; Ge, Baolan; Ma, Qingbian; Yang, Jianzhong; Chen, Fengying; Mi, Yuhong; Zhu, Huadong; Wang, Cong; Li, Yan; Zhang, Hongbo; Yang, Rongjia; Guan, Jian; et al.
Abstract A survey was performed to assess the current management of targeted temperature management (TTM) in patients following cardiac arrest (CA) and whether healthcare providers will change target temperature after publication of 2015 American Heart Association guidelines for resuscitation in China. 52 hospitals were selected from whole of China between August to November 2016. All healthcare providers in EMs and/or ICUs of selected hospitals participated in the study. 1952 respondents fulfilled the survey (86.8%). TTM in CA patients was declared by 14.5% of physicians and 6.7% of the nurses. Only 4 of 64 departments, 7.8% of physicians and 5.7% of the nurses had implemented TH for CA patients. Since the publication of 2015 AHA guidelines, 33.6% of respondents declared no modification of target temperature, whereas 51.5% declared a target temperature's change in future practice. Respondents were more likely to choose 35∼36 °C-TTM (54.7%) after guidelines publication, as compared to that before guidelines publication they preferred 32∼34 °C-TTM (54.0%). TTM for CA patients was still in the early stage in China. Publication of 2015 resuscitation guidelines did have impact on choice of target temperature among healthcare providers. They preferred 35∼36 °C-TTM after guidelines publication.